The Filler Effect: The Influence of Filler Content and Surface Area on Cementitious Reaction Rates. Issue 6 (15th March 2013) - Oey, Tandré; Kumar, Aditya; Bullard, Jeffrey W.; Neithalath, Narayanan; Sant, Gaurav
Abstract : Finely ground mineral powders are known to accelerate cement hydration rates. This "filler effect" has been attributed to the effects of dilution (w/c increase) when the cement content is reduced or to the provision of additional surface area by fine powders. The latter contribution (i.e., surface area increase) is speculated to provide additional sites for the nucleation of the hydration products, which accelerates reactions. Through extensive experimentation and simulation this study describes the influence of surface area and mineral type (e.g., quartz or limestone) on cement reaction rates. Simulations using a boundary nucleation and growth (BNG) model and a multiphase reaction ensemble (MRE) indicate that the extent of the acceleration is linked to the: (1) magnitude of surface area increase and (2a) capacity of the filler's surface to offer favorable nucleation sites for hydration products. Other simulations using a kinetic cellular automaton model (HydratiCA) suggest that accelerations are linked to: (2b) the interfacial properties of the filler that alters (increases or decreases) its tendency to serve as a nucleant, and (3) the chemical composition of the filler and the tendency for its dissociated ions to participate in exchange reactions with the calcium silicate hydrate product. The simulations are correlated with accelerations observed using isothermal calorimetry when fillers partially replace cement. The research correlates and unifies the fundamental parameters that drive the filler effect and provides a mechanistic understanding of the influence of filler agents on cementitious reaction rates.